UV–VIS optical spectroscopy investigation on the kinetics of long-lived RONS produced by a surface DBD plasma source. (24th September 2019) - Simoncelli, Emanuele; Schulpen, Jeff; Barletta, Federica; Laurita, Romolo; Colombo, Vittorio; Nikiforov, Anton; Gherardi, Matteo
Abstract: The analysis of the gas phase chemistry of a cold atmospheric plasma is a fundamental step for a more thorough understanding of the effects it can induce on target substrates. This work aims at investigating, by means of optical spectroscopic techniques, the kinetics of O3, NO2 and NO3 produced by a Surface Dielectric Barrier Discharge. The phenomenon of discharge poisoning (or ozone quenching ) in static ambient air was investigated varying the electrical power density applied to the plasma source. Kinetics of the reactive oxygen and nitrogen species production were obtained by means of time resolved UV/VIS optical absorption spectroscopy and highlighted how the discharge poisoning takes place once the applied power density ovecomes a critical value of 0.11 W cm −2 . An ozone-enriched atmosphere (with a maximum O3 density around 3000–4000 ppm) is thus obtained when the source is operated below the critical power density, while a NO x -enriched atmosphere (highest concentrations of NO2 around 1250 ppm and NO3 around 35 ppm) is obtained at higher applied power densities. Moreover, since the production of NO, one of the most important quenchers of O3, is directly related to the vibrational energy of nitrogen molecules, the vibrational population of N2, determined by processing emission spectra of N2 (B → C) band, was studied. Finally, considerations regarding both the energy cost of production of a reactive oxygen species and reactive nitrogen species atmosphere and the possibility of on-line monitoring its chemical composition, were presented in order to emphasize the potential of optical absorption spectroscopy techniques for the on-line control of plasma assisted industrial processes.